2019
DOI: 10.1038/s41377-019-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Nature-inspired chiral metasurfaces for circular polarization detection and full-Stokes polarimetric measurements

Abstract: The manipulation and characterization of light polarization states are essential for many applications in quantum communication and computing, spectroscopy, bioinspired navigation, and imaging. Chiral metamaterials and metasurfaces facilitate ultracompact devices for circularly polarized light generation, manipulation, and detection. Herein, we report bioinspired chiral metasurfaces with both strong chiral optical effects and low insertion loss. We experimentally demonstrated submicron-thick circularly polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(159 citation statements)
references
References 50 publications
0
159
0
Order By: Relevance
“…Surface plasmons, collective electron density oscillations at dielectric/ metal interfaces, [26][27][28][29][30] can dramatically enhance chiroptical responses by concentrating far-field electromagnetic waves into subwavelength volumes. [31][32][33][34][35][36][37] Over the past decade, many studies have demonstrated the feasibility of transferring molecular chirality to plasmonic nanostructures, [16,18,19,38,39] opening up a plethora of possibilities for chiral biosensing and bioimaging with unprecedented detection limits ideally down to the singlemolecule regime. A primary driving force behind this development is the breakthrough in design and fabrication of artificial metallic nanostructures, ranging from top-down techniques such as focused ion beam milling, [40] electron-beam lithography [41] and direct laser writing, [42] to bottom-up methods like chemical synthesis and self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasmons, collective electron density oscillations at dielectric/ metal interfaces, [26][27][28][29][30] can dramatically enhance chiroptical responses by concentrating far-field electromagnetic waves into subwavelength volumes. [31][32][33][34][35][36][37] Over the past decade, many studies have demonstrated the feasibility of transferring molecular chirality to plasmonic nanostructures, [16,18,19,38,39] opening up a plethora of possibilities for chiral biosensing and bioimaging with unprecedented detection limits ideally down to the singlemolecule regime. A primary driving force behind this development is the breakthrough in design and fabrication of artificial metallic nanostructures, ranging from top-down techniques such as focused ion beam milling, [40] electron-beam lithography [41] and direct laser writing, [42] to bottom-up methods like chemical synthesis and self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral metamaterials and metasurfaces [1][2][3][4][5] have recently attracted much attention in the community of nanophotonics due to their practical applications for circular dichroism (CD), [6][7][8][9][10][11] polarization conversion, [12] chiral biosensing and imaging, [13][14][15] polarimetric detection, [16] spin-controlled wavefront shaping, [17,18] and asymmetric transmission. [10,18,19] Spin-selective optical responses can also be obtained in intrinsically achiral metasurfaces due to extrinsic chirality by the experimental arrangement different from their mirror image [20] and even by the direct phase modulation depending on the handedness of circular polarization of the incident wave.…”
Section: Introductionmentioning
confidence: 99%
“…The second example is by Shi et al [186] who studied the silver ants living in the Saharan desert and developed an idea of a biomimetic metasurface-based coating for the passive effective cooling of objects. The third example is by Basiri et al [187] who designed a metasurface-based polarization filter device inspired by the polarization sensing of the compound eyes of mantis shrimps. The peak extinction ratio of the metasurface device could reach a value of 35, and transmission efficiency was close to 80% in the near-infrared wavelength region.…”
Section: Future Directionsmentioning
confidence: 99%